Nilsson, Christina - Grotjahn, Rebecca (Die Musik in Geschichte und Gegenwart. Supplementband)

Die AdressatInnen sozialräumlich orientierter Sozialer Arbeit und der Sozialraum als Adressat – eine empirische Betrachtung - Klingler, Birte; Landhäußer, Sandra; Ziegler, Holger (Soziale Arbeit in Gesellschaft)
Die Bielefelder Arbeitsgruppe 8 Sozialarbeit/Sozialpädagogik hat in den letzten vier Dekaden deutliche Markierungen in der deutschsprachigen wie der internationalen Debatte um Soziale Arbeit gesetzt. Antriebsmotor dieser Entwicklung war und ist Hans-Uwe Otto. In diesem Band haben sich dessen Ko-Autorinnen und -Autoren aus Anlass seiner Pensionierung erstmals zu einer Gesamtschau dieser 'Bielefelder Forschungsperspektiven' auf die Soziale Arbeit versammelt. Die acht zentralen Forschungs- und Themenfelder, die von der Bielefelder AG oder unter ihrer Beteiligung in den letzten Jahrzehnten bestellt wurden, gliedern den Band. Der gemeinsame Bezugspunkt aller hier versammelten Beiträge ist die Verbindung von Sozialer Arbeit und Gesellschaft: Soziale Arbeit als professionelle Instanz ist nur in ihrem gesellschaftlichen Kontext und damit in explizit gesellschaftspolitischer Positionierung realisierbar.
Keywords: Sozialraum; Soziale Arbeit

Biomimetic Synthesis of Resorcylate Natural Products Utilizing Late Stage Aromatization: Concise Total Syntheses of the Marine Antifungal Agents 15G256ι and 15G256β - Navarro, Ismael; Basset, Jean-François; Hebbe, Séverine; Major, Sarah M.; Werner, Thomas; Howsham, Catherine; Bräckow, Jan; Barrett, Anthony G. M. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Zwischen (trügerischer) Ruhe und fieberhafter Arbeit – Betreuung von Blended-Learning-Seminaren - Göddertz, Nina; van Treeck, Timo; Wieg, Mirco (Online Tutoring Journal, Ausgabe 2 (9))
Keywords: ILIAS; Jugendforschung

Tuning of the Optical Properties in Photonic Crystals Made of Macroporous Silicon - Kitzerow, Heinz-Siegfried; Matthias, Heinrich; Schweizer, Stefan L.; van Driel, Henry M.; Wehrspohn, Ralf B. (Advances in Optical Technologies)
It is well known that robust and reliable photonic crystal structures can be manufactured with very high precision by electrochemical etching of silicon wafers, which results in two- and three-dimensional photonic crystals made of macroporous silicon. However, tuning of the photonic properties is necessary in order to apply these promising structures in integrated optical devices. For this purpose, different effects have been studied, such as the infiltration with addressable dielectric liquids (liquid crystals), the utilization of Kerr-like nonlinearities of the silicon, or free-charge carrier injection by means of linear (one-photon) and nonlinear (two-photon) absorptions. The present article provides a review, critical discussion, and perspectives about state-of-the-art tuning capabilities.

Recent Advances in Coherent Optical OFDM High-Speed Transmission - Nazarathy, Moshe; Noé, Reinhold; Weidenfeld, Rakefet; Khurgin, Jacob; Meiman, Yehouda; Cho, Pak; Shpantzer, Isaac (2008 IEEE PHOTONICSGLOBAL@SINGAPORE (IPGC), VOLS 1 AND 2)

Optical 5 krad/s endless polarisation tracking - Hidayat, A.; Koch, B.; Mirvoda, V.; Zhang, H.; Lichtinger, A.; Sandel, D.; Noé, Reinhold (ELECTRONICS LETTERS)

Homogeneous Administration of Experiments in Material Science for Configuration, Monitoring and Analysis - Ferber, Ferdinand; Gockel, Franz-Barthold; Hampel, Thorsten; Pawlak, Thorsten; Mahnken, Rolf (Experimental Analysis of Nano and Engineering Materials and Structures)

Geometry update driven by material forces for simulation of brittle crack growth in functionally graded materials - Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

On the stabilization of tetrahedral finite elements using volume and area bubble functions - Caylak, Ismail; Mahnken, Rolf (PAMM)

Experimentelle Untersuchungen zum Thermoschock beim Hybridumformprozess - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Simulation of asymmetric effects for shape memory alloys - Wilmanns, Stefan; Mahnken, Rolf (PAMM)

Fast optical endless polarization tracking with LiNbO3 component - Hidayat, A.; Koch, B.; Mirvoda, V.; Zhang, H.; Bhandare, S.; Ibrahim, S. K.; Sandel, D.; Noé, Reinhold (2008 CONFERENCE ON OPTICAL FIBER COMMUNICATION/NATIONAL FIBER OPTIC ENGINEERS CONFERENCE, VOLS 1-8)

A Limit Relation for Dunkl-Bessel Functions of Type A and B - Rösler, Margit; Voit, Michael (Symmetry, Integrability and Geometry: Methods and Applications)
Keywords: Geometry and Topology; Mathematical Physics; Analysis

Meditationen, Geheimnisse, Zufälle: Messiaens Konzept der langage communicable - Grotjahn, Rebecca (organ. Journal für die Orgel)

Multiple-Channel Signal Detection using the Generalized Coherence spectrum - Ramírez, D.; Vía, J.; Santamaría, I. (Proc.\ IAPR Work. Cognitive Information Process.)
Recently, a generalization of the magnitude squared coherence (MSC) spectrum for more than two random processes has been proposed. The generalized MSC (GMSC) spectrum definition, which is based on the largest eigenvalue of a matrix containing all the pairwise complex coherence spectra, provides a frequency-dependent measure of the linear relationship among several stationary random processes. Moreover, it can be easily estimated by solving a generalized eigenvalue problem. In this paper we apply the GMSC spectrum for detecting the presence of a common signal from a set of linearly distorted and noisy observations. Specifically, the new statistic for the multiple-channel detection problem is the integral of the square root of the GMSC, which can be estimated as the sum of the $P$ largest generalized canonical correlations (typically $P=1$ is enough in practice). Unlike previous approaches, the new statistic implicitly takes into account the spectral characteristics of the signal to be detected (e.g., its bandwidth). Finally, the performance of the proposed detector is compared in terms of its receiver operating characteristic (ROC) curve with the generalized coherence (GC) showing a clear improvement in most scenarios.

Performance analysis of OFDM-IDMA systems with peak-power limitation - Tong, Jun; Guo, Qinghua; Ping, Li (IEEE 10th\ Int.\ Symp.\ Spread Spectrum Techn.\ & Appl.)
This paper is concerned with orthogonal frequencydivision multiplexing interleave-division multiple-access (OFDMIDMA) systems over frequency-selective fading channels. Deliberate clipping is applied to reduce the peak-to-average power ratio (PAPR) of each user’s transmitted signal. An iterative multiuser detection (MUD) technique is developed to recover the performance loss due to clipping. A semi-analytical signal-to-noise ratio (SNR) evolution technique is proposed, which can provide quick and accurate prediction of the iterative MUD performance. Numerical results show that the performance of OFDM-IDMA is not sensitive to the frequency selectivity of channels, and OFDM-IDMA is more power-efficient than other alternative multi-carrier transmission techniques

Impact of signaling schemes on iterative linear minimum-mean-square-error detection - Ping, Li; Tong, Jun; Yuan, Xiaojun; Guo, Qinghua (Proc.\ IEEE Global Telecomm.\ Conf.)
In this paper, we study the iterative detection problem for a coded system with multi-ary modulation. We show that, with iterative linear minimum-mean-square-error (LMMSE) detection, superposition coded modulation (SCM) can provide performance superior to that with other traditional signaling schemes used in trellis coded modulation (TCM) and bit-interleaved coded modulation (BICM). This finding provides a useful guideline for system design considering inter-symbol interference (ISI) and other forms of interference. Simulation results are provided to illustrate the efficiency of the iterative LMMSE detection with different signaling schemes.

Bounds on the Degree of Impropriety of Complex Random Vectors - Schreier, Peter J. (IEEE Signal Process.\ Lett.)
A complex random vector is called improper if it is correlated with its complex conjugate. We introduce a measure for the degree of impropriety, which is a function of the canonical correlations between the vector and its complex conjugate (sometimes called the circularity spectrum). This measure is invariant under linear transformation, and it relates the entropy of an improper Gaussian random vector to its corresponding proper version. For vectors with given spectrum, we present upper and lower bounds on the attainable degree of impropriety, in terms of the eigenvalues of the augmented covariance matrix.

A time-frequency formula for LMMSE filters for nonstationary underspread continuous-time stochastic processes - Wahlberg, Patrik; Schreier, Peter J. (Proc. 16th\ European Signal Process.\ Conf.)
We study linear minimum mean square error (LMMSE) filters for estimating a nonstationary second-order continuous-time stochastic process from a noisy observation. The equation for the optimal filter is treated in the Weyl symbol domain, and the involved Weyl symbols are assumed to belong to certain modulation spaces. By discretizing this equation using a Gabor frame we transform it into a matrix equation and obtain a formula for the filter by matrix inversion. The inverse matrix has off-diagonal decay at a rate that increases the more underspread the process is.

Bericht zum XXI. Deutschen Kongress für Philosophie ‚Lebenswelt und Wissenschaft' - Essen, 15.-19.09.2008 - Alpsancar, Suzana; Denker, Kai; Kaminski, Andreas; Rölli, Marc; Sabrowski, Maxine; Hetzel, Andreas

Paartanz als nonverbale Kommunikation und sein (Inter-?) Subjekt. Theoretische Skizze eines Forschungsvorhabens. - Haller, Melanie; Fleischle-Braun, Claudia; Stabel (Hg.), Ralf (TanzForschung und TanzAusbildung. Dokumentation des Jubiläumssymposiums der Gesellschaft für Tanzforschung im Oktober 2007, Hamburg, S. 132-139)

Café Buenos Aires und Galeria del Latino. Zur Translokalität und Hybridität städtischer Tanzkulturen - Haller, Melanie; Funke-Wieneke, Jürgen; Klein (Hg.), Gabriele (Bewegungsraum und Stadtkultur. Sozial- und kulturwissenschaftliche Perspektiven, Bielefeld 2008, S.51-74 (zusammen mit Gabriele Klein))

Die 'Natur der Subjekte'. Subjektivierungsprozesse im Tanz - Haller, Melanie; Rehberg (Hg.), Karl-Siegbert (Die Natur der Gesellschaft. Verhandlungen des 33. Kongresses der Deutschen Gesellschaft für Soziologie 2006), Frankfurt a. M., S. 2734-2747 (zusammen mit Gabriele Klein))

Der einzelne Schritt wird zum Erlebnis“ oder warum tanzt der Mensch - Haller, Melanie (In: Ästhetik und Kommunikation, Hf. 146, 40 Jahrgang, S. 96-97)

The impact of minimum taxation by an imputable wealth tax on capital budgeting and business strategy of German companies - Sureth-Sloane, Caren; Maiterth, Ralf (Review of Managerial Science)

Steuern und Risikobereitschaft in Modellen irreversibler Investitionen - Niemann, Rainer; Sureth-Sloane, Caren (Journal für Betriebswirtschaft)

UV-photopolymerisation of poly(methyl methacrylate)-based inorganic–organic hybrid coatings and bulk samples reinforced with methacrylate-modified zirconium oxocluster - Graziola, Francesco; Girardi, Fabrizio; Bauer, Matthias; Di Maggio, Rosa; Rovezzi, Mauro; Bertagnolli, Helmut; Sada, Cinzia; Rossetto, Gilberto; Gross, Silvia (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Toward Designing a Robot that Learns Actions from Parental Demonstrations - Nagai, Yukie; Muhl, Claudia; Rohlfing, Katharina (The 2008 IEEE International Conference on Robotics and Automation)
How to teach actions to a robot as well as how a robot learns actions is an important issue to be discussed in designing robot learning systems. Inspired by human parent-infant interaction, we hypothesize that a robot equipped with infant-like abilities can take advantage of parental proper teaching. Parents are known to significantly alter their infant-directed actions versus adult-directed ones, e.g. make more pauses between movements, which is assumed to aid the infants’ understanding of the actions. As a first step, we analyzed parental actions using a primal attention model. The model based on visual saliency can detect likely important locations in a scene without employing any knowledge about the actions or the environment. Our statistical analysis revealed that the model was able to extract meaningful structures of the actions, e.g. the initial and final state of the actions and the significant state changes in them, which were highlighted by parental action modifications. We further discuss the issue of designing an infant-like robot that can induce parent-like teaching, and present a human-robot interaction experiment evaluating our robot simulation equipped with the saliency model.
Keywords: icra08

“Try something else!” — When users change their discursive behavior in human-robot interaction - Lohse, Manja; Rohlfing, Katharina; Wrede, Britta; Sagerer, Gerhard
This paper investigates the influence of feedback provided by an autonomous robot (BIRON) on users’ discursive behavior. A user study is described during which users show objects to the robot. The results of the experiment indicate, that the robot’s verbal feedback utterances cause the humans to adapt their own way of speaking. The changes in users’ verbal behavior are due to their beliefs about the robots knowledge and abilities. In this paper they are identified and grouped. Moreover, the data implies variations in user behavior regarding gestures. Unlike speech, the robot was not able to give feedback with gestures. Due to the lack of feedback, users did not seem to have a consistent mental representation of the robot’s abilities to recognize gestures. As a result, changes between different gestures are interpreted to be unconscious variations accompanying speech.
Keywords: discursive behavior; autonomous robot; BIRON; man-machine systems; robot abilities; robot knowledge; user gestures; robot verbal feedback utterance; speech processing; user verbal behavior; service robots; human-robot interaction; human computer interaction; gesture recognition

Parental Action Modification Highlighting the Goal versus the Means - Nagai, Yukie; Rohlfing, Katharina (The IEEE 7th International Conference on Development and Learning)
Parents significantly alter their infant-directed actions compared to adult-directed ones, which is assumed to assist the infants’ processing of the actions. This paper discusses differences in parental action modification depending on whether the goal or the means is more crucial. When demonstrating a task to an infant, parents try to emphasize the important aspects of the task by suppressing or adding their movement. Our hypothesis is that in a goal-crucial task, the initial and final states of the task should be highlighted by parental actions, whereas in a means-crucial task the movement is underlined. Our analysis using a saliency-based attention model partially verified it: When focusing on the goal, parents tended to emphasize the initial and final states of the objects used in the task by taking a long pause before/after they started/fulfilled the task. When focusing on the means, parents shook the object to highlight it, which consequently made its state invisible. We discuss our findings regarding the uniqueness and commonality of the parental action modification. We also describe our contribution to the development of robots capable of imitating human actions.

Cognitive Foundations - Rohlfing, Katharina (Handbook of Communication Competence)

Computational Analysis of Motionese: What can infants learn from parental actions? - Nagai, Yukie; Rohlfing, Katharina (The 16th International Conference on Infant Studies)

Language acquisition — a multimodal avenue - Rohlfing, Katharina (The Bielefeld Introduction to Applied Linguistics)

Single-photon level ultrafast all-optical switching - Han, Xiao-Feng; Weng, Yu-Xiang; Wang, Rui; Chen, Xi-Hao; Luo, Kai Hong; Wu, Ling-An; Zhao, Jimin (Applied Physics Letters)

Multikriteriale Zielerreichung im naturwissenschaftsbezogenen Sachunterricht der Grundschule – Eine Studie zum Einfluss von Strukturierung in schülerorientierten Lehr-Lernumgebungen auf das Erreichen kognitiver, motivationaler und selbstbezogener Zielsetzungen. Inaugural-Dissertation zur Erlangung des akademischen Grades des Doktors in den Erziehungswissenschaften an der Westfälischen Wilhelms-Universität Münster - Blumberg, Eva

Rätsel und Lektüren: Zur Zyklizität von Robert Schumanns Liederkreis Myrthen op. 25 - Grotjahn, Rebecca (Gattungsgeschichte als Kulturgeschichte. Festschrift für Arnfried Edler)

Fundstück: Musikwissenschaftliche Genderforschung im 19. Jahrhundert? - Grotjahn, Rebecca (Feste - Opern - Prozessionen)

Eine ‚Stimme von fast männlicher Färbung – Zarah Leander und die nationalsozialistische Geschlechterordnung - Grotjahn, Rebecca (Performativität und Performance. Geschlecht in Musik, Theater und MedienKunst)

Der Wirkungskreis des Weibes. Zur Funktion frauenfeindlicher Rede in der Zauberflöte - Grotjahn, Rebecca (Wider die Frau. Zur Geschichte und Funktion misogyner Rede)

Optimal MIMO transmission schemes with adaptive antenna combining in the RF path - Santamaría, I.; Elvira, V.; Vía, J.; Ramírez, D.; Pérez, J.; Ibáñez, J.; Eickhoff, R.; Ellinger, F. (Proc.\ Eur.\ Signal Process.\ Conf.)
In this paper we study space-time coding schemes for a novel MIMO transceiver which performs adaptive signal combining in radio-frequency (RF). The limitations of the RF circuitry make necessary to develop specific designs for this architecture. For instance, the space and time encoders must operate separately (the former works in the RF domain and the latter works in baseband), and at different time scales: the spatial encoder or RF beamformer must remain fixed dur- ing the transmission of a probably large number of symbols, whereas the time-encoder can work at the symbol rate. We show in the paper that although the multiplexing gain of the system is limited to one, we are still able to achieve the full spatial diversity of the MIMO channel as well as to increase the received signal-to-noise ratio through array gain. Specifically, when perfect channel state information (CSI) is available only at the receiver we propose to use a scheme referred to as orthogonal beam division multiplexing (OBDM). With this scheme the symbols are time-precoded with a unitary discrete Fourier transform (DFT) matrix, then they are successively transmitted through orthogonal direc- tions and, finally, we use a receiver comprising maximal ra- tio combining (MRC) followed by a minimum mean-square error (MMSE) decoder. The performance of the proposed techniques in terms of outage capacity and bit error rate is illustrated by means of several simulations examples.

Spectral Relations for Multidimensional Complex Improper Stationary and (Almost) Cyclostationary Processes - Wahlberg, Patrik; Schreier, Peter J. (IEEE Trans.\ Inform.\ Theory)
We study continuous-time multidimensional wide- sense stationary (WSS) and (almost) cyclostationary processes in the frequency domain. Under the assumption that the correlation function is uniformly continuous, we prove the existence of a unique sequence of spectral measures, which coincide with the restrictions to certain subdiagonals of the spectral measure in the strongly harmonizable case. Moreover, the off-diagonal measures are absolutely continuous with respect to the diagonal measure. As a consequence, for strongly harmonizable scalar improper almost cyclostationary processes, we obtain representation formulas for the components of the complementary spectral measure and the off-diagonal components of the spectral measure, in terms of the diagonal component of the spectral measure. We apply these results to analytic signals, which produces sufficient conditions for propriety for almost cyclostationary analytic signals.

Analysis and design of OFDM-IDMA systems - Tong, Jun; Guo, Qinghua; Ping, Li (European Trans.\ Comm.)
This paper deals with the analysis and design of orthogonal frequency-division multiplexing interleave-division multiple-access (OFDM-IDMA). We begin with the analysis of the information-theoretical advantages of non-orthogonal transmission schemes in fading multiple-access channels. We then turn attention to practical design issues. A signal-to-noise ratio (SNR) evolution technique is developed to predict the bit-error-rate (BER) performance of OFDM-IDMA. This technique is applied to system design and optimisation. Through proper power allocation, OFDM-IDMA can achieve the multi-user gain (MUG) predicted by information-theoretical analysis. It is also an attractive option in compensating for the clipping effect caused by peak-power limitation. Numerical examples show that OFDM-IDMA can (i) alleviate the PAPR problem commonly suffered by OFDM-based schemes; (ii) deliver significant MUG compared with other orthogonal alternatives; (iii) provide robust communications in frequency-selective channels; and (iv) support high single-user throughput. Copyright {©} 2008 John Wiley & Sons, Ltd.

A Unifying Discussion of Correlation Analysis for Complex Random Vectors - Schreier, Peter J. (IEEE Trans.\ Signal\ Process.)
The assessment of multivariate association between two complex random vectors is considered. A number of correlation coefficients based on three popular correlation analysis techniques, namely canonical correlation analysis, multivariate linear regression, and partial least squares, are reviewed and connected to performance measures in signal processing and communications, such as mean-squared estimation error, mutual information, and signal-to-noise ratio (SNR). For complex data, there are three types of correlation coefficients, which account for rotational, reflectional, and total (i.e., rotational and reflectional) dependencies between two random vectors. These three types are defined and analyzed for different correlation coefficients, and a numerical example is given. It is often required to compare two complex random vectors in a lower-dimensional subspace. For the large class of increasing, Schur-convex correlation coefficients, it is shown that the low-rank approximations of two random vectors maximizing a particular correlation coefficient are determined only by the constraints imposed on the correlation analysis technique. In this context, the correlation spread is defined as a normalized measure of how much of the overall correlation is contained in a low-dimensional subspace.

Polarization Ellipse Analysis of Nonstationary Random Signals - Schreier, Peter J. (IEEE Trans.\ Signal\ Process.)
We present a novel way of extending rotary-component and polarization analysis to nonstationary random signals. If a complex signal is resolved into counterclockwise and clockwise rotating phasors at one particular frequency only, it traces out an ellipse in the complex plane. Rotary-component analysis characterizes this ellipse in terms of its shape and orientation. Polarization analysis looks at the coherence between counterclockwise and clockwise rotating phasors and whether there is a preferred rotation direction of the ellipse (counterclockwise or clockwise). In the nonstationary case, we replace this ellipse with a time-dependent local ellipse that, at a given time instant, gives the best local approximation of the signal from a given frequency component. This local ellipse is then analyzed in terms of its shape, orientation, and degree of polarization. A time-frequency coherence measures how well the local ellipse approximates the signal. The ellipse parameters and the time-frequency coherence can be expressed in terms of the Rihaczek time-frequency distribution. Under coordinate rotation, the ellipse shape, the degree of polarization, and the time-frequency coherence are invariant, and the ellipse orientation is covariant. The methods presented in this paper provide an alternative to ellipse decompositions based on wavelet ridge analysis.

A generalization of the magnitude squared coherence spectrum for more than two signals: definition, properties and estimation - Ramírez, D.; Vía, J.; Santamaría, I. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
The coherence spectrum is a well-known measure of the linear statistical relationship between two time series. In this paper, we extend this concept to several processes and define the generalized magnitude squared coherence (GMSC) spectrum as a function of the largest eigenvalue of a matrix containing all the pairwise complex coherence spectra. The GMSC is bounded between zero and one, and attains its maximum when all the processes are perfectly correlated at a given frequency. Furthermore, three different GMSC spectrum estimators, extending those previously proposed for the MSC of two processes, are presented. Specifically, we compare the Welch method, the minimum variance distortionless response (MVDR) estimator and a new estimator based on canonical correlation analysis (CCA).

Performance analysis of multi-ary systems with iterative linear minimum-mean-square-error detection - Ping, Li; Tong, Jun; Yuan, Xiaojun; Guo, Qinghua (5th\ Int.\ Symp.\ Turbo Codes & Rel.\ Top.)
This paper is concerned with coded multi-ary systems over linear channels. Based on a semi-analytical evolution technique, the impact of signaling schemes on the performance of low-cost iterative linear minimum-mean-square-error (LMMSE) detection is studied. It is shown that superposition coded modulation (SCM) maximizes the output signal-to-noise ratio (SNR) of LMMSE detectors. Consequently, SCM may potentially outperform other conventional signaling schemes when LMMSE detectors are used. Numerical examples are provided to verify the theoretical analysis.

A comparative study of STBC transmissions at 2.4 GHz over indoor channels using a $2 × 2$ MIMO testbed - Ramírez, D.; Santamaría, I.; Pérez, J.; Vía, J.; García-Naya, J. A.; Fernández-Caramés, T. M.; Pérez-Iglesias, H.; López, M. González; Castedo, L.; Torres-Royo, J. M. (Wireless Comm. and Mobile Computing)

Iterative detection techniques for clipped OFDM systems - Tong, Jun; Ping, Li (Proc.\ IEEE Global Telecomm.\ Conf.)
This paper studies orthogonal frequency-division multiplexing (OFDM) systems employing coded modulation. Clipping is applied to reduce the peak-to-average-power-ratio (PAPR) of the transmit signal. A soft compensation method is proposed to combat the clipping effect. It is shown that the proposed method can outperform conventional clipping effect mitigation methods. The impact of signaling schemes of the coded modulation on system performance is investigated. The average variance analysis and numerical results demonstrate that superposition coded modulation (SCM) together with the proposed detection technique provides a simple and efficient solution to clipped OFDM transmission.

The degree of impropriety (noncircularity) of complex random vectors - Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
A complex random vector is called improper (noncircular) if it is correlated with its complex conjugate. We consider measures for the degree of impropriety that are invariant under linear transformation. These measures are functions of the canonical correlations between the vector and its complex conjugate, which have been termed the circularity coefficients. However, we show that these circularity coefficients do not tell the whole story: Two random vectors with identical covariance matrix and identical circularity coefficients can still behave differently in second-order estimation and detection.

Forschungsergebnisse in der Betriebswirtschaftlichen Steuerlehre — eine Bestandsaufnahme - Hundsdoerfer, Jochen; Kiesewetter, Dirk; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Microemulsion approach to neodymium, europium, and ytterbium oxide/hydroxide colloids—Effects of precursors and preparation parameters on particle size and crystallinity - Rill, Christoph; Bauer, Matthias; Bertagnolli, Helmut; Kickelbick, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Platinum species in the pores of NaX, NaY and NaA zeolites studied using EPR, XAS and FTIR spectroscopies - Akdogan, Yasar; Vogt, Christina; Bauer, Matthias; Bertagnolli, Helmut; Giurgiu, Liviu; Roduner, Emil (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Ordered Mesoporous Thin Films of Rutile TiO2 Nanocrystals Mixed with Amorphous Ta2O5 - Wu, Jin-Ming; Antonietti, Markus; Gross, Silvia; Bauer, Matthias; Smarsly, Bernd M. (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Erste Ergebnisse zur Messung pädagogischer Kompetenz in der universitären Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas (Tagung „Kompetenzdiagnose und Kompetenzentwicklung in der Lehrerbildung“ des CEVET und PLAZ)

Messung erziehungswissenschaftlicher Kompetenz in der Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas; Hilligus, Annegret Helen; Grafe, Silke (AEPF-Tagung „Kompetenz – Modellierung – Diagnostik – Entwicklung – Förderung“)

Hans Werner Henzes „Bassariden“ im Kontext der 68er-Bewegung - Tumat, Antje (Musikkulturen in der Revolte. Studien zu Rock, Avantgarde und Klassik im ‚Umfeld’ von 1968)

Einleitung - Tumat, Antje (Von Volkston und Romantik: „Des Knaben Wunderhorn“ in der Musik)

Das Libretto zu „Demofoonte“. Die Oper zur Einweihung des Ludwigsburger Opernhauses - Tumat, Antje (Schlosstheater Ludwigsburg. 250 Jahre – Von der Hofoper zum lebendigen Theaterdenkmal)

Von Volkston und Romantik: „Des Knaben Wunderhorn“ in der Musik

Zwischen Oper und Filmmusik: Erich Wolfgang Korngolds Musiken zu William Shakespeares „Viel Lärmen um Nichts“ und Hans Müllers „Der Vampir oder die Gejagten“ - Tumat, Antje (Erich Wolfgang Korngold – Wunderkind der Moderne oder letzter Romantiker?)

Mozart und die Schauspielmusik - Tumat, Antje (Bericht über den Kongress Der junge Mozart: 1756-1780, Philologie – Analyse – Rezeption)

Alban Berg - Tumat, Antje (Killy Literaturlexikon. Autoren und Werke des deutschsprachigen Kulturraumes.)

Women’s Organisations and the Reshaping of the Public Sphere: A Comparative Analysis - Spiegel, Anna; Dannecker, Petra (Negotiating Development in Muslim Societies: Gendered Spaces and Translocal Connections)

Negotiating Women’s Rights in a Translocal Space. Women’s Organisations and Networking in Malaysia - Spiegel, Anna (Negotiating Development in Muslim Societies: Gendered Spaces and Translocal Connections)

Smoking reduces serum levels of lamotrigine. - Reinsberger, Claus; Dorn, T; Krämer, G (Seizure)

Depression of human corticospinal excitability induced by magnetic theta-burst stimulation: evidence of rapid polarity-reversing metaplasticity. - Gentner, R; Wankerl, K; Reinsberger, Claus; Zeller, D; Classen, J (Cereb Cortex)

Analysis of the Nucleation and Growth of Amorphous CaCO3 by Means of Time-Resolved Static Light Scattering - Liu, Jianing; Rieger, Jens; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Review of “Wikinomics“ (Don Tapscott & Anthony D. Williams) - Fuchs, Christian (Journal of Communication)

Internet and Society: Social Theory in the Information Age (Hardcover) - Fuchs, Christian

Dialektisches Denken als Grundlage der Kritik des transnationalen informationellen Kapitalismus (Dialectical thinking as foundation for the critique of transnational informational capitalism) - Fuchs, Christian (Proceedings of the conference „Polyphone Dialektik“ (Polyphonous Dialectics), Berlin, November 1-4, 2007. Vorschein 30)

Review Essay of “Wikinomics: How Mass cCllaboration Changes Everything“, by Don Tapscott and Anthony D. Williams - Fuchs, Christian (International Journal of Communication 2 (2008), Review Section: 1-11)

Towards a Critical Theory of Information - Fuchs, Christian (Qué es información? (What is information?) In Proceedings of the First International Meeting of Experts in Information Theories. An Interdisciplinary Approach (Primer Encuentro Internacional de Expertos Teorías de la Información. Un enfoque interdisciplinar))

Muster mustern – Das Muster als Attraktor der Wahrnehmung - Kraft, Kerstin

Dielectric layers for organic field effect transistors as gate dielectric and surface passivation - Diekmann, T.; Pannemann, C.; Hilleringmann, Ulrich (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Noise propagation for induced fast transient impulses on PCB-level - Taki, M.; John, W.; Hedayat, C.; Hilleringmann, Ulrich (2007 18th International Zurich Symposium on Electromagnetic Compatibility)

Der Geist Gottes swingte über den Wassern. Unerhörte Bestimmungen zwischen Musik und Religione - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/52/hsw8.htm)

Leid und Lied oder: Das Gesetz als Bedingung des Daseins. Der Moses des dänischen Komponisten Herman David Koppel (1908-1988) - Schroeter-Wittke, Harald (Praktische Theologie)

Sind Schöpfungsglaube und Evolutionstheorie kompatibel? - Schroeter-Wittke, Harald (Verband evangelischer Religionslehrerinnen und -lehrer an Berufskollegs in Westfalen e.V. Rundbrief 2008)

daZWISCHENteit. Communicare - Kunst und Kirche in Warburg - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/52/hsw9.htm)

Werten lernen - Ethik und Pädagogik aus protestantischer Sicht - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

20 Blicke auf das Jesuskind. Zum 100. Geburtstag von Olivier Messiaen (1908-1992) - Schroeter-Wittke, Harald (Praktische Theologie)

Mass in D. Zum 150. Geburtstag von Ethel Smyth (1858-1944) - Schroeter-Wittke, Harald (Praktische Theologie)

Oscar Peterson's Easter Suite - Schroeter-Wittke, Harald (Praktische Theologie)

Wilhelm Gräb / Birgit Weyel (Hg.): Handbuch Praktische Theologie, Gütersloh 2007 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Direct determination of exciton homogeneous and inhomogeneous linewidths in semiconductor quantum wells with two-dimensional fourier transform spectroscopy - Meier, Torsten; Zhang, Tianhao; Bristow, Alan D.; Dai, Xingcan; Kuznetsova, Irina; Thomas, P.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Homogeneous and inhomogeneous broadening of heavy- and light-hole excitons in semiconductor quantum wells are measured along with the excitation dependence of both broadenings. Isolation of disorder-induced broadening is possible with spectra in different coherent pathways.

Intensity dependence of charge and spin currents generated by ultrafast two-color photoexcitation of semiconductor quantum wells - Meier, Torsten; Duc, Huynh Thanh; Koch, S.W.; Pasenow, B. (72nd annual meeting and DPG spring meeting of the Condensed Matter Section and the Divisions)

Influence of heavy-hole light-hole band mixing on the strength of optically generated spin-currents in III-V semiconductor quantum wells - Meier, Torsten; Koch, S.W.; Pasenow, B. (72nd annual meeting and DPG spring meeting of the Condensed Matter Section and the Divisions)

High harmonics generated in semiconductor nanostructures by the coupled dynamics of optical inter- and intraband excitations - Golde, D.; Meier, Torsten; Koch, S. W. (Physical Review B)
The emitted radiation from semiconductor nanostructures due to the excitation with intense ultrashort optical laser pulses is analyzed. Semiconductor Bloch equations that consistently describe the coupled light-field-induced interband and intraband dynamics are solved numerically. It is demonstrated that the intraband dynamics considerably influences the light emission in the regime of extreme nonlinear optics. In particular, the intraband acceleration significantly modifies the dynamics of the interband polarization which results in a strong enhancement of high-harmonic generation.

Microscopic Analysis of the Optical and Electronic Properties of Semiconductor Photonic-Crystal Structures - Meier, Torsten; Pasenow, B.; Reichelt, Matthias; Stroucken, T. (Nanophotonic Materials: Photonic Crystals, Plasmonics, and Metamaterials)

Peter Stamms Erzählen von Identität in Räumen des Dazwischen - Müller, Inez (Zwischen Globalisierungen und Regionalisierungen)

Editor of a special issue on "ICTs and Society: PhD Students' Transdisciplinary Research Projects" (Proceedings of the PhD conference “ICTs and Society“, June 20-21, 2008, University of Salzburg) - Fuchs, Christian (triplec (Cognition, Communication, Co- operation))

Introduction to the special issue on "ICTs and Society: PhD Students’ Transdisciplinary Research Projects" - Fuchs, Christian (tripleC (Cognition, Communication, Co-operation))

Sociology, Dynamic Critical Realism, and Radical Constructivism - Fuchs, Christian (Constructivist Foundations. (Comment on the article “Who Conceives of Society?“ by Ernst von Glasersfeld that was published in the same issue))

Positivism, Postmodernism, or Critical Theory? A Case Study of Communications Students’ Understandings of Criticism - Fuchs, Christian; Sandoval, Marisol (Journal for Critical Education Policy Studies)

The Implications of New Information and Communication Technologies for Sustainability - Fuchs, Christian (Environment, Development and Sustainability)

Africa and the Digital Divide - Fuchs, Christian; Horak, Eva (Telematics and Informatics)

Perspectives of Cyberethics in the Information Society - Bichler, Robert; Fuchs, Christian; Raffl, Celina (Framing Evil)

The Web as Techno-Social System. The Emergence of Web 3.0 - Raffl, Celina; Hofkirchner, Wolfgang; Fuchs, Christian; Schafranek, Matthias (Cybernetics and Systems 2008)

Foundations and Two Models of Guaranteed Basic Income - Fuchs, Christian (Perspectives on Work)